Familiarity, attitudes, and self-regulatory challenges related to mindfulness - MRAZEK, Alissa J. (Institutional Knowledge at Singapore Management University, 2020)
Objectives: Despite growing evidence demonstrating the benefits of mindfulness for physical and mental health, little is known about the barriers that dissuade individuals from practicing mindfulness. The present study sought to examine the self-regulatory barriers that most commonly prevent mid-life adults from engaging in mindfulness practice. Methods: The present study surveyed a nationally representative sample of 385 mid-life adults (ages 50-64) in the USA to assess familiarity, attitudes, and prior experiences with mindfulness, as well as self-regulatory challenges that may hinder consistent practice. Specifically, this research focused on the self-regulatory elements of (i) goal setting, (ii) limiting beliefs, (iii) habit formation, (iv) willingness to engage, and (v) self-monitoring. Results: Findings demonstrated that 79% of mid-life adults are familiar with the term mindfulness, yet only 34% are confident in their understanding of the term. Despite this lack of confidence, associations with the term were fairly positive, and the majority of mid-life adults expressed having tried to incorporate mindfulness into their lives. Due to this familiarity, positive perception, and attempted incorporation, one might expect that adopting a consistent mindfulness practice would be an easy next step. However, there was an indication that dramatically fewer individuals had taken the key self-regulatory steps toward developing a consistent mindfulness practice. Conclusions: This study revealed key self-regulatory challenges, such as failing to set a specific goal and create a habit, that may interfere with mid-life adults adopting a consistent mindfulness practice. Implications of these challenges are discussed, particularly for intervention design and education.